2013
DOI: 10.1111/jop.12114
|View full text |Cite
|
Sign up to set email alerts
|

DNA repair gene polymorphisms and risk of head and neck cancer in the Tunisian population

Abstract: Altered activity of DNA repair enzymes may be involved in modulating cancer susceptibility and pathogenesis of head and neck cancer (HNC). We conducted a case-control study to test the association between three common single-nucleotide polymorphisms of XRCC1, ERCC2, and ERCC3 genes with HNC risk in Tunisian patients. To the best of our knowle dge, this is the first report on polymorphisms in XRCC1, ERCC2, and ERCC3 and susceptibility to HNC in our population. The genotype analyses of XRCC1 Arg399Gln, ERCC2 Lys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 36 publications
(45 reference statements)
1
12
0
Order By: Relevance
“…We also found no association of XRCC1 c.839G>A and c.1196G>A SNPs with OPSCC risk, according to previous results from overall HNSCC studies (Sturgis et al 1999;Tae et al 2004;Demokan et al 2005;Matullo et al 2006;Li et al 2007;Harth et al 2008;Applebaum et al 2009;Csejtei et al 2009;Kowalski et al 2009;Gugatschka et al 2011;Al-Hadyan et al 2012;Yuan et al 2012). In contrast, the variant allele A of c.1196G>A SNP was associated with decreased risk (Olshan et al 2002;Kumar et al 2012;Khlifi et al 2014) and increased risk (Choudhury et al 2014) of overall HNSCC. The disparate results obtained in our study and previous studies may be, again, attributed to different HN tumor sites investigated in previous studies, since similar frequencies of the genotypes were seen in our control group and in the other controls.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…We also found no association of XRCC1 c.839G>A and c.1196G>A SNPs with OPSCC risk, according to previous results from overall HNSCC studies (Sturgis et al 1999;Tae et al 2004;Demokan et al 2005;Matullo et al 2006;Li et al 2007;Harth et al 2008;Applebaum et al 2009;Csejtei et al 2009;Kowalski et al 2009;Gugatschka et al 2011;Al-Hadyan et al 2012;Yuan et al 2012). In contrast, the variant allele A of c.1196G>A SNP was associated with decreased risk (Olshan et al 2002;Kumar et al 2012;Khlifi et al 2014) and increased risk (Choudhury et al 2014) of overall HNSCC. The disparate results obtained in our study and previous studies may be, again, attributed to different HN tumor sites investigated in previous studies, since similar frequencies of the genotypes were seen in our control group and in the other controls.…”
Section: Discussionsupporting
confidence: 59%
“…The roles of the OGG1 c.977C>G (Elahi et al 2002;Zhang et al 2004;Matullo et al 2006;Görgens et al 2007;Hall et al 2007;Kumar et al 2011;Mitra et al 2011), APEX1 c.444T>G (Matullo et al 2006;Li et al 2007); XRCC1 c.-77T>C, c.580C>T (Sturgis et al 1999;Olshan et al 2002;Tae et al 2004;Demokan et al 2005;Matullo et al 2006;Applebaum et al 2009;Csejtei et al 2009;Kowalski et al 2009;Gugatschka et al 2011;Kumar et al 2012), c.839G>A (Tae et al 2004;Applebaum et al 2009;Gugatschka et al 2011;Kumar et al 2012) and c.1196G>A (Sturgis et al 1999;Olshan et al 2002;Tae et al 2004;Demokan et al 2005;Matullo et al 2006;Li et al 2007;Harth et al 2008;Applebaum et al 2009;Csejtei et al 2009;Kowalski et al 2009;Gugatschka et al 2011;AlHadyan et al 2012;Kumar et al 2012;Yuan et al 2012;Choudhury et al 2014;Khlifi et al 2014) SNPs in overall HNSCC risk are still controversial or unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a meta analysis done by Flores-Obando et al [25] [33]. Khlifi R et al, (2013) reported that only the XRCC1 Arg 399 Gln polymorphism was associated with the risk of HNC in the Tunisian population (OR = 2.04; P = 0.001) [34]. Similarly, Mazumder et al [35] reported Figure 1.…”
Section: Base Excision Repair (Ber)mentioning
confidence: 96%
“…Many previous epidemiologic studies have been conducted to examine the association between ERCC2 and ERCC3 gene polymorphisms and risk of cancers, such as lung, endometrial, head and neck, and laryngeal cancer (Hu et al, 2006;Doherty et al, 2011;Sakoda et al, 2012;Khlifi et al, 2014;Lu et al, 2014). Hu et al (2006) conducted a case-control study in a Chinese population, and found that ERCC2 and ERCC3 gene polymorphisms contribute to the development of lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that ERCC2 and ERCC3 gene polymorphisms do not contribute to the development of this type of cancer. Khlifi et al (2014) investigated the role of ERCC2 and ERCC3 gene polymorphisms on susceptibility to head and neck cancer, and they observed no statistically significant association between the risk of head and neck cancers and the two gene polymorphisms. Lu et al (2014) conducted a case-control study in a Chinese population, and suggested that ERCC2 and ERCC3 polymorphisms contribute to the development of laryngeal cancer.…”
Section: Discussionmentioning
confidence: 99%